Kelayakan Penyampaian Materi Dakwah Filsafat Ketuhanan Kepada Remaja Pendekatan Teori Perkembangan Kognitif - Sutriyono, Sutriyono; Hidayat, Ahmad; Pradesa, Dedy (INTELEKSIA: Jurnal Pengembangan Ilmu Dakwah, 2023)
FEASIBILITY OF DELIVERING DIVINE PHILOSOPHY DAKWAH MATERIAL TO ADOLESCENTS APPROACH TO COGNITIVE DEVELOPMENT THEORY. This study examines the feasibility of delivering da’wah material about Divinity using philosophical and scientific approach to moslem teenage high school students. Its motivated by the problem of juvenile delinquency which requires Islamic divinity da’wah as a basia for teenage moral development. So far, the delivary of Islamic Divinity material has been mostly indoctrinative and normative approach. It couldn’t develop critical thinking in teenagers. Meanwhile, in society there was Atheism thought that used scientific theories as its argue. Da’wah of Islamic divinity using philosophical approach could be an alternatif to counter Atheism arguments and strengthening the faith of Muslim teenagers. How is the conveying da’wah material of philosophy Islamic divinity to teenagers? It would be approached using cognitive development theory. It method is qualitative research, data resouces using related literature and observations of da’wah activities to teenagers. The results showed that acoording to cognitive development theory delivering Islamic divinity da’wah material using philosophical and scientific approach is appropriate for teenage high school students. This is in line with the cognitive development of teenagers. Its also in line with material target, load, and content. The methods are relevant to the characteristics of teenagers. Its proven have positive social impact.